Evaluation of the Efficacy and Safety of the Neonatal Sepsis Risk Calculator in a Tertiary Referral Center in Lebanon - Neaimeh, Yara; Ard, Natasha; Daher, Darine; Abourjeili, Joseph; Makki, Maha; Tamim, Hani; Maalouf, Faouzi I. (Journal of Pediatric Infectious Diseases, 2024)
Objective Early onset sepsis (EOS) is a significant cause of morbidity and mortality in the newborn period. This has led to overinvestigation and antibiotic overuse, which remains a concern in EOS management. Sepsis risk calculator (SRC), a tool validated in American and European populations, aids physicians in sepsis risk stratification and has been shown to decrease antibiotics overuse for EOS. The aim of the study was to evaluate the efficacy and safety of the SRC in a tertiary referral center in Lebanon.Methods This was a single-center retrospective cohort study, conducted at a tertiary medical center in Beirut, Lebanon, that included infants born at more than 34 weeks' gestational age between January 1, 2017 and January 1, 2019. Data was collected on risk factors for neonatal sepsis and the clinical management performed on each newborn. The SRC was used to calculate a sepsis risk score for each patient. Comparison between actual management performed and SRC recommendation was measured.Results We reviewed 3,085 charts, out of which 257 charts were excluded. Patients were stratified into two groups: high sepsis risk and low sepsis risk. Out of the 2,828 patients included, 81 infants (2.9%) had high risk of sepsis, out of which 2 patients had positive blood cultures. There were no patients with a low SRC score who had positive blood cultures. There were no patients who were supposed to receive antibiotics per the SRC recommendation who did not undergo workup for sepsis. Implementing SRC would have prevented antibiotics administration in 42 (1.5%) patients.Conclusion SRC was adequately capable of detecting neonates with sepsis without missing actual cases of EOS, providing initial support for its safety in the population studied. Implementing the SRC would result in reduced usage of antibiotics, laboratory tests, and admissions to the neonatal intensive care unit.
Keywords: neonatal sepsis; clinical evaluation; sepsis risk calculator; antibiotic stewardship